Effectiveness and Interactivity on the Use of Virtual Learning Environment (VLE) in Scouting Course - Trinovandhi Setyawan; Nurcholis Istiawan (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2021)
This study aims at determining university students’ perceptions on the use of Virtual Learning Environment (VLE) in Scouting Course, specifically focusing on the learning effectiveness and interactivity aspects. VLE based learning has been implemented in the even semester of 2020 during the pandemic of Covid-19. This descriptive qualitative study took 40 students of Physical Education, Health, and Recreation Study Program of IKIP Budi Utomo Malang as the research sample. The results of the questionnaire analysis showed positive perception from the students in regard to Scouting Course using VLE, seen from the aspects of learning effectiveness (76.2%) and learning interactivity (80.4%). However, there were some challenges in achieving a more conducive virtual learning environment. For instance, the unstable network conditions, lack of students' initial knowledge of ICT, incompatible devices with the default system of VLE application, and one-way learning (predominantly assignments). Nevertheless, further research on the effectiveness of other VLE applications and student learning strategies are suggested.